Therapeutic Efficacy of Antibiotics in Chronic Canine Otitis Externa - Nainika; Pardeep Sharma; Rajendra D Patil; Prasenjit Dhar; Amit Kumar (The Indian Veterinary Journal, 2024)
Canine otitis externa is inflammation of external ear canal, causing discomfort to the patients. In presented study dogs displaying symptoms of otitis externa for a duration exceeding two months were studied. Twenty-three dogs were included based on the duration of illness. Cytological and microbiological investigations were conducted in all the cases.Animals were categorized into two groups for treatment. Group I (n=11) was given oral Marbofloxacin, while Group II (n=12) received Cefpodoxime. The therapeutic efficacy was assessed on days 7th and 14th post-treatment. Notably, Group I demonstrated rapid and effective recovery within 14 days compared to Group II.